Stability of Buriti Oil Microencapsulated in Mixtures of Azuki and Lima Bean Flours with Maltodextrin - Fuzetti, Caroline Gregoli [UNESP]; Nicoletti, Vânia Regina [UNESP] (MDPI, 2024)
Buriti oil (Mauritia flexuosa L.) is rich in carotenoids, mainly β-carotene, and has great value for application as a food, pharmaceutical, or cosmetic ingredient, as well as a natural pigment. Microencapsulation is a promising technique to protect compounds sensitive to degradation such as β-carotene. Materials composed of carbohydrates and proteins, such as azuki bean (Vigna angularis L.) and lima bean (Phaseolus lunatus L.) flours, are alternative matrices for microencapsulation, which additionally provide good amounts of nutrients. In combination with maltodextrin, the flours represent a protective barrier in stabilizing lipophilic compounds such as buriti oil for subsequent spray drying. In this work, the performance of mixtures of maltodextrin with whole azuki and lima bean flours was evaluated in the microencapsulation of buriti oil. The microcapsules showed good results for solubility (>80%), hygroscopicity (~7%), encapsulation efficiency (43.52 to 51.94%), and carotenoid retention (64.13 to 77.49%.) After 77 days of storage, the microcapsules produced maintained 87.79% and 90.16% of carotenoids, indicating that the powders have high potential for application as encapsulants in the food and pharmaceutical industries.
Keywords: carotenoids; Mauritia flexuosaL; microencapsulation; Phaseolus lunatusL; pulses; Vigna angularisL